Factors affecting attitude towards knowledge sharing among employees in South City Plaza, Seri Kembangan / Wan Nurul 'Ain Shaheeda Wan Mohd Mayeeddin Qahar - Wan Mohd Mayeeddin Qahar, Wan Nurul 'Ain Shaheeda (2016)
The main objective of this study is to investigate the factors affecting attitude towards knowledge sharing. This study has been conducted at South City Plaza, Seri Kembangan and it is mainly for identifying the factors affecting attitude towards knowledge sharing among employees. A sample of 72 employees have being selected from a population size of 130 employees. Questionnaire is used to collect the data and information about this issue from employees. Then, the data obtained from the respondents are analyze by using Statistical Package for the Social Sciences (SPSS) software. From the analysis being done, it revealed that there is a significant relationship between reduced workload and knowledge feedback towards attitude towards knowledge sharing. However, losing face, employee rewards and enhanced personal relationship does not have a significant relationship with attitude towards knowledge sharing. Other than that, this study also provides recommendations for either organization or manager and for future researchers where these recommendations can help them to improve and solve the problem regarding attitude towards knowledge sharing.